Analisis Yuridis Terhadap Perjanjian Kerja Waktu Tertentu (PKWT) “UD. Permata Furni” - Ulfi Nihaya; Achmad Busro (Magister Kenotariatan Universitas Diponegoro, 2022)
AbstractProtection for workers is very necessary in order to provide basic rights for every worker, to guarantee equal opportunities and grants in general, in order to realize the welfare of workers. Therefore, work agreements must be in accordance with the law so that their use can provide fair rights for workers. The purpose of this paper is to find out and analyze work agreements, especially work agreements for a certain time (PKWT) between workers and “UD. Furni Gems